1999
DOI: 10.1051/aas:1999386
|View full text |Cite
|
Sign up to set email alerts
|

Rate coefficients for electron impact excitation of S xv

Abstract: Collision strengths for electron impact excitation of S xv are calculated in a close-coupling approach. The nineteen lowest LS states are included in the calculation. Rate coefficients are obtained for transitions from the ground 1s 2 1 S 0 state to the fine-structure levels of all excited states of 1s2 ( = 0, 1) and 1s3 ( = 0, 1, 2) configurations. The resulting effective collision strengths are fitted to a polynomial function of log(T e /K), and rate coefficients are presented in the temperature range betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…As mentioned in the introduction, some groups (Zhang and Sampson 1987, Pradhan 1985, Keenan et al 1987, Norrington et al 1998, Kimura et al 1999 reported effective collision strengths for S 14+ , Ca 18+ and Fe 24+ . A comparison is made between the present and the previous results.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…As mentioned in the introduction, some groups (Zhang and Sampson 1987, Pradhan 1985, Keenan et al 1987, Norrington et al 1998, Kimura et al 1999 reported effective collision strengths for S 14+ , Ca 18+ and Fe 24+ . A comparison is made between the present and the previous results.…”
Section: Resultsmentioning
confidence: 97%
“…However, the analysis of the satellite data requires collision data between the fine-structure levels. Kimura et al (1999) made calculations of fine-structure cross sections with the use of termcoupling coefficients to include the intermediate-coupling effects. The calculations are based on those of Nakazaki et al (1993).…”
Section: Introductionmentioning
confidence: 99%
“…As has been shown for He-like Fe XXV (Kimura et al 1999, Machado-Pelaez et al 2002 the resonances arising from the complex n = N + 1 have a strong effect on transitions to the complex n = N. Along with the full calculation including all the 31 fine-structure states up to n = 4, we considered a smaller target model, including all 17 levels up to n = 3 to compare the effect of the resonances. Figures 6-8 show the effective collision strengths for transitions from the ground state to the n = 2 levels, as well as transitions among levels of the n = 2 complex, and transitions from the ground level and levels of the n = 2 complex to levels of the n = 3 complex.…”
Section: Effective Collision Strengthsmentioning
confidence: 99%
“…[28] The collision strengths are averaged over a Maxwellian distribution of electron velocities to obtain the effective collision strength. For excitation from initial level i to final level f , the effective collision strength Υ if at electron temperature T e (in Kelvin) is given by [29]…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Once the effective collision strength is determined, the excitation rate coefficient at electron temperature T e (in Kelvin) is given as [29]…”
Section: Theoretical Methodsmentioning
confidence: 99%